2021
DOI: 10.2174/1871520621999210104201242
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic, Antiproliferative and Antioxidant Properties of Sea Grape Leaf Extract Fractions (Coccoloba uvifera L.)

Abstract: Background: Cancer is a disease characterized by the invasion and uncontrolled growth of cells. One of the best ways to minimize the harmful effects of mutagens is through the use of natural antimutagens. In this regard, the search for new antimutagens that act in the chemoprevention could represent a promising field in this area. Objective: In this study biological potential of 11 fractions from Coccoloba uvifera L. leaf hexane extract was evaluated by several in vitro tests. Methods: Leaves were lyophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
5
10
0
Order By: Relevance
“…Antimutagenic compounds contribute to cancer prevention, because they decrease the concentration of mutagens, blocking mutagens before they damage DNA. [47] The inhibition of spontaneous revertants obtained in this research is higher than the previously reported fractions of jackfruit methanol-hexane extract at 50 mg/mL [48] and similar to fresh [47] and microencapsulated sea grape leaves extract in nanofibers of gelatin/agave fructans, [49] both at 20 μg/plate. The sea grape leaves extract is rich in triterpenes such as lupeol and eucomic, piscidic, caffeic, ferulic, and quinic organic acids.…”
Section: Antimutagenic Activitysupporting
confidence: 58%
See 3 more Smart Citations
“…Antimutagenic compounds contribute to cancer prevention, because they decrease the concentration of mutagens, blocking mutagens before they damage DNA. [47] The inhibition of spontaneous revertants obtained in this research is higher than the previously reported fractions of jackfruit methanol-hexane extract at 50 mg/mL [48] and similar to fresh [47] and microencapsulated sea grape leaves extract in nanofibers of gelatin/agave fructans, [49] both at 20 μg/plate. The sea grape leaves extract is rich in triterpenes such as lupeol and eucomic, piscidic, caffeic, ferulic, and quinic organic acids.…”
Section: Antimutagenic Activitysupporting
confidence: 58%
“…The inhibition of spontaneous revertants obtained in this research is higher than the previously reported fractions of jackfruit methanol‐hexane extract at 50 mg/mL [48] and similar to fresh [47] and microencapsulated sea grape leaves extract in nanofibers of gelatin/agave fructans, [49] both at 20 μg/plate. The sea grape leaves extract is rich in triterpenes such as lupeol and eucomic, piscidic, caffeic, ferulic, and quinic organic acids [47] . The differences in the antimutagenic activity between this and other studies are associated with the source and type of compounds present in the extracts, purity degree, extraction method, and so on.…”
Section: Resultssupporting
confidence: 41%
See 2 more Smart Citations
“…These compounds are of great biological interest since they offer great benefits to the consumers, such as, anti-inflammatory, anti-cancer, and gastroprotective. Ramos-Hernández et al [10], identified fractions of lupeol, acecetin, and βsitosterol of sea grape extract by column chromatography purification. These compounds possess antimutagenic, antiproliferative, and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%